Functional complementation of a yeast knockout strain by Schistosoma mansoni Rho1 GTPase in the presence of caffeine, an agent that affects mutants defective in the protein kinase C signal transduction pathway - Pedro HN de Aguiar; Débora N Santos; Francisco P Lobo; Túlio M Santos; Andréa M Macedo; Sérgio DJ Pena; Carlos R Machado; Glória R Franco (Memorias do Instituto Oswaldo Cruz, 2006)
In a previous study, the Schistosoma mansoni Rho1 protein was able to complement Rho1 null mutant Saccharomyces cerevisiae cells at restrictive temperatures and under osmotic stress (low calcium concentration) better than the human homologue (RhoA). It is known that under osmotic stress, the S. cerevisiae Rho1 triggers two distinct pathways: activation of the membrane 1,3-beta-glucan synthase enzymatic complex and activation of the protein kinase C1 signal transduction pathway, promoting the transcription of response genes. In the present work the SmRho1 protein and its mutants smrho1E97P, smrho1L101T, and smrho1E97P, L101T were used to try to clarify the basis for the differential complementation of Rho1 knockout yeast strain by the human and S. mansoni genes. Experiments of functional complementation in the presence of caffeine and in the presence of the osmotic regulator sorbitol were conducted. SmRho1 and its mutants showed a differential complementation of the yeast cells in the presence of caffeine, since smrho1E97P and smrho1E97P, L101T mutants showed a delay in the growth when compared to the yeast complemented with the wild type SmRho1. However, in the presence of sorbitol and caffeine the wild type SmRho1 and mutants showed a similar complementation phenotype, as they allowed yeast growth in all caffeine concentrations tested.